Kualitas Pelayanan terhadap Kepuasan Pelanggan Pada Aplikasi Pesan Antar Makanan - Enny Diah Astuti; Nika Sintesa (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
Digital Business is experiencing rapid growth, including in the online-based food business. The Internet is creating a new face in interactive communication between sellers, consumers and business partners. This allows the company to be able to interact and work together continuously to be able to develop products, marketing, delivery and maximum service to get customer satisfaction. One type of business that is currently growing rapidly and is very popular with customers is food delivery services including go food, grab food and shopee food. This delivery service will increasingly compete according to the response from customers, influenced by the quality of service. The purpose of this study was to find out how service quality affects customer satisfaction, especially in online- based food delivery applications. The research used in this research is quantitative analysis method. The method used is to collect information obtained from questionnaires. Variable indicators were tested for validity and reliability. In testing this validity using the Pearson Correlation approach. The reliability test in this study used Cronbach, Alpha coefficient. The results of the study explain that the service variable partially has a positive effect on customer satisfaction. The influence of service quality provided by service providers and service partners is very well responded by application users.